(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
Every day, thousands of women and children are trafficked. India is a country that is both a transit and a destination in the broader context of trafficking in South Asia. There is some trafficking from India to the Gulf States and Southeast Asia, in addition to a significant amount of trafficking within the country. Within the nation, there is also the sale of children and their trans-state transit. A report released by the National Human Rights Commission of India claims that 11,000 children go missing out of 40,000 kidnappings annually. According to non-governmental organizations, every year, the sex trade involves the trafficking of between 12,000 and 50,000 women and children into the country from adjacent countries. National Commission for Women declared in 1997 In Bombay alone, 40 000 girls between the ages of 10-16 years were selling their bodies from their doorsteps. MAITI Nepal published in September 1999 that there are about 1 to 2 lakh Nepali girls in Indian brothels alone, with about 5-7 thousand being sold every year. Another report suggests that more than 40,000 girls in the Calcutta Sonargachhi red light area are Nepalese. But all these figures are related to prostitution; very little information is available on the other forms of trafficking. According to ILO estimates, 21 million people are enslaved or forced into employment. Among them, one in four are said to be younger than eighteen. It is believed that 5.5 million children are trafficked globally. They experience abuse, exploitation, and violence, which leads to forced labour, prostitution, begging, and armed recruitment. Approximately one in six of the over 28,800 children that were reported to NCMEC in 2023 were probably the victims of child sex trafficking. Aim: The primary focus of this article is the many purposes for which children are trafficked from India, as well as the criminal crimes associated with this issue. Overall, the majority of minors are abducted for sexual offences and sold to wealthy individuals across international criminal networks. Recommended eradicating the nation’s black scars related to child abuse and trafficking.